A 14 bp promoter element directs the testis specificity of the Drosophila beta 2 tubulin gene. - Michiels, F (1989)
To analyze the regulation of gene expression during male germ cell development, we investigated the testis-specific expression of the Drosophila beta 2 tubulin gene. Germ line transformation experiments with the upstream region of the D.melanogaster beta 2 tubulin gene fused to the Escherichia coli lacZ gene resulted in the correct tissue specific expression of the reporter gene. Furthermore, we showed that the upstream sequences of the beta 2 tubulin gene of the distantly related species D.hydei can drive the expression of the lacZ gene testis specifically in D.melanogaster flies. A detailed deletion analysis showed that 53 bp of upstream and 23 bp (D.melanogaster) or 29 bp (D.hydei) of leader sequences are sufficient to confer tissue specificity. The short promoter regions contain a 14 bp motif at identical positions in both species, which acts as a position-dependent promoter element. In vitro mutagenesis and subsequent germline transformation experiments revealed that this sequence is the only element necessary for the testis-specific transcription of the beta 2 tubulin gene in Drosophila.